Neoadjuvant chemoradiotherapy for stage III (N2/3) non-small-cell lung cancer: a review of prospective studies. (February 2013) - Robinson, Cliff; Stephans, Kevin
SUMMARY Trimodality therapy, a maximal combination of chemotherapy, radiotherapy and surgical resection, for stage III non-small-cell lung cancer promises improved outcomes through optimizing local, regional and distant control. Phase II trials of neoadjuvant chemoradiotherapy have explored a number of different radiotherapy dose and fractionation schemes, and have identified an important subset of patients who achieve mediastinal nodal clearance and may achieve long-term survival. Phase III trials of various combinations of chemotherapy, radiotherapy and surgery have demonstrated mixed results with regard to each modality's impact on progression-free or overall survival. In this review, we focus on the historical lessons learned from prospective trials of trimodality therapy completed over the last 30 years and set the stage for future studies of neoadjuvant chemoradiotherapy for stage III non-small-cell lung cancer.